One-year results from the Assessing MICRO-vascular resistances via IMR to predict outcome in ST-elevation myocardial infarction patients with multivessel disease undergoing primary PCI (AMICRO) trial - Fineschi, Massimo; Verna, Edoardo; Barioli, Alberto; Mezzapelle, Giuseppe; Bartolini, Davide; Turiano, Giovanni; Guiducci, Vincenzo; Manari, Antonio; Lucarelli, Katya; Uguccioni, Lucia; Repetto, Alessandra; Tarantini, Giuseppe (Frontiers in Cardiovascular Medicine, 2022)
Background: In ST-elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary angioplasty (PPCI) the index of microcirculatory resistance (IMR) correlates to the extent of myocardial damage and left ventricular (LV) function recovery. Data on the IMR time-course and impact on clinical outcome in STEMI patients with multi-vessel disease (MVD) are scarce. Aims: We designed a prospective, multicenter clinical trial to assess the infarct-related artery (IRA)-IMR in STEMI patients with MVD undergoing PPCI and to explore its potential in relationship with outcome and LV remodeling. Methods: The study enrolled 242 STEMI patients with MVD. Both fractional flow reserve (FFR) and IMR of the IRA were assessed after successful PPCI. Then, FFR/IMR measurements were repeated in the IRA at a staged angiography, and FFR-guided angioplasty was performed in non-IRA lesions. The primary endpoint was the composite of cardiovascular death, re-infarction, re-hospitalization for heart failure, resuscitation or appropriate ICD shock at 1-year follow-up. Results: A significant improvement of IRA-IMR values (from 47.9 to 34.2, p<0.0001) was observed early after PPCI. Staged FFR-guided angioplasty was performed in 102 non-IRA lesions. We failed to find a correlation between IRA-IMR, clinical events and LV remodeling. Notwithstanding, in patients with anterior STEMI an inverse correlation between initial IMR values and LV function at follow-up was observed. Conclusions: After successful PPCI, a significant proportion of patients with STEMI and MVD had coronary microvascular dysfunction as assessed by IMR that recovered early after reperfusion. Higher IMR values predicted lack of improvement of LV function only in anterior STEMI.